Design thinking : understanding how designers think and work / Nigel Cross. - Cross, Nigel, 1942- (Bloomsbury Visual Arts, 2023)
What do designers do during the activity of 'designing'? How are creative thinking skills employed? What is design ability and how is it developed? Nigel Cross, one of design's foremost scholars, explores through observation, analysis and reflection the often enigmatic elements of design thinking. Detailed case studies provide commentary on specific examples of design innovation and development, with interspersed chapters providing research-based overviews of design cognition. This new edition expands on the previous book with more emphasis on teamwork and co-design, and updated and expanded case studies and examples - including the development of a Formula One car and a backpack for mountain biking - as well as a new glossary of key terms. Written for all those wanting to understand more about how good designers work, regardless of discipline.